Governing for Diversity: An Exploration of Practitioners' Urban Forest Preferences and Implications for Equitable Governance - Sax, Daniel; Manson, Corbin; Nesbitt, Lorien (Frontiers in Sustainable Cities, 2020)
Urban forests are increasingly acknowledged as sources of multiple benefits and central to climate resilience and human well-being. Given these diverse and significant benefits, it is important to govern urban forests so as to ensure that all residents have equitable access and enjoyment. Understanding urban forest preferences, and including them in planning and management, is a key aspect of informed and contextually relevant urban forest governance. Although many studies have examined public urban forest preferences, we lack an understanding of the preferences of a key stakeholder: urban foresters. This study presents the results of semi-structured interviews with 22 urban forestry and allied green practitioners focused on preferred and least-preferred aspects of the urban forest. Participants expressed their preferred urban forest characteristics according to four themes: administration, spatial attributes, naturalness, and social benefits. Least-preferred characteristics were expressed under the themes of administration and degradation. Results suggest that practitioners employ a systems-level lens when discussing urban forest preferences. However, they also draw on personal experience when constructing their preferences, particularly in relation to naturalness and spatial diversity. These results provide insight into the urban forest preferences of practitioners and highlight the importance of innovative approaches, such as mosaic governance in urban forestry, to facilitate a just integration of the diverse preferences of urban forest stakeholders.